Artifical Intelligence in Cyber Security in Morocco - Zahra, Ayach Fatima; Supandi, Supandi; Wijayanto, Wijayanto (Universitas Ivet, 2024)
: Morocco had more than 56,000 cyberattacks directed towards mobile devices, as to a recent report by Russian cybersecurity company Kaspersky. Attacks against mobile devices increased significantly worldwide in 2023, amounting to 33.7 million and rising at a sweeping yearly average of 52%. Documentation research is the methodology employed in this study. It is a method of qualitative research. This means that rather than quantifying data, it focuses on comprehending and interpreting human experiences, behaviors, and views. The researcher investigates text-based materials (such as journal articles and internet media) to gain a better understanding of artificial intelligence in cybersecurity. Morocco has made significant advances in cybersecurity thanks to the combined efforts of different stakeholders, including the government, law enforcement, regulatory authorities, cybersecurity groups, the commercial sector, academia, international partners, and civil society. These efforts began with the development of the first